Morphological diversity in SDH-deficient renal carcinomas: a three-case exploration of variant features and dedifferentiation - Sánta, Fanni; Dabaghian, Antranik; Pósfai, Boglárka; Vasas, Béla; Kaizer, László; Jenei, Alex; Scheich, Bálint; Téglási, Vanda; Sápi, Zoltán; Bíró, Krisztina; Maráz, Anikó; Stelios, Mavrogenis; et al. (Virchows Archiv, 2024)
Succinate dehydrogenase (SDH)-deficient renal cell carcinoma (RCC) is a rare subtype of renal neoplasm predominantly affecting younger individuals. It is characterized by germline mutations in SDHx genes, particularly type B. Histologically, SDH-deficient RCC features eosinophilic cytoplasmic cells forming solid nests or microcysts, sometimes entrapping normal tubules. We present three SDH-deficient RCC cases with overlapping morphological features with fumarate hydratase-deficient RCC and TFEB-rearranged RCC, an appearance that has not been previously described. All tumors lacked SDHB expression and harbored pathogenic SDHB mutations, with the germline nature confirmed in two cases. Metastasis developed in two patients. Our case set highlights the diagnostic challenges of molecularly defined renal tumors and expands the morphological spectrum of SDH-deficient RCC with unusual histological features. Clinically, these tumors appear to be aggressive.
Keywords: senioři; Succinate dehydrogenase; Carcinoma, Renal Cell; Cell Dedifferentiation; SDHB; lidé; Middle Aged; mužské pohlaví; sukcinátdehydrogenasa; karcinom z renálních buněk; Adult; Renal cell carcinoma; RCC; Kidney Neoplasms; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Biomarkers, Tumor; nádorové biomarkery; Humans; transkripční faktory BHLH-Zip; lidé středního věku; fumarasa; Succinate Dehydrogenase; dediferenciace buněk; dospělí; zárodečné mutace; Aged; Germ-Line Mutation; nádory ledvin; Male; Fumarate Hydratase